DEVELOPMENT OF MASSAGE CHAIR MADE OF CARDBOARD MATERIALS: DESIGN, FABRICATION, AND STRENGTH EVALUATION - Zulaikah, Siti; Triawan , Farid; Budiman , Bentang Arief; Romadhon , Yusuf (Jurnal Rekayasa Mesin, 2024)
This study aims to design and fabricate a prototype of massage chair made of corrugated cardboard materials and evaluate its structural strength. It could be a pioneering study as no one had manifested or discussed it before. The prototype is currently made with dimensions of approximately 60 ´ 50 ´ 100 cm, consisting of 6 cardboard components, affords a reflexology sensation from solid rubber balls, and provides reclinable features at the backrest and footrest. The most prominent benefit of this cardboard massage chair compared to the commercialized ones is environmentally friendly and lightweight products. Moreover, the constructed component can be disassembled and folded, making it a portable massage chair. From the strength evaluation, the cardboard massage chair can still endure a load of 50 kg to the prototype’s seat, backrest, and footrest. However, multi loading directions (e.g., vertical, longitudinal, lateral), stress concentration, and fluctuating person weight would generate tremendous stress and lead to a more substantial possibility of damage and failures on the cardboard after several testing cycles. Therefore, further improvement processes should be investigated to develop an optimized version of cardboard massage chair in the future.